2018
DOI: 10.1103/physrevb.97.224412
|View full text |Cite
|
Sign up to set email alerts
|

Subnanosecond magnetization reversal of a magnetic nanoparticle driven by a chirp microwave field pulse

Abstract: We investigate the magnetization reversal of single-domain magnetic nanoparticle driven by linear down-chirp microwave magnetic field pulse. Numerical simulations based on the Landau-Lifshitz-Gilbert equation reveal that solely down-chirp pulse is capable of inducing subnanosecond magnetization reversal. With certain range of initial frequency and chirp rate, the required field amplitude is much smaller than that of constant-frequency microwave field. The fast reversal is because the down-chirp microwave field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…It has been shown that the fast magnetization reversal is achieved by DCMWP 42 with the physical picture: the frequency of DCMWP roughly matches the frequency change of magnetization precession. Hence, it triggers inefficient stimulated microwave absorption (emission) by (from) the magnetization before (after) it crosses over the energy barrier.…”
Section: Analytical Model and Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…It has been shown that the fast magnetization reversal is achieved by DCMWP 42 with the physical picture: the frequency of DCMWP roughly matches the frequency change of magnetization precession. Hence, it triggers inefficient stimulated microwave absorption (emission) by (from) the magnetization before (after) it crosses over the energy barrier.…”
Section: Analytical Model and Methodsmentioning
confidence: 69%
“…However, a recent study 42,43 demonstrated the fast and power-efficient magnetization reversal of a cubic shaped nanoparticle (i.e., with zero demagnetization/shape anisotropy field) by the circularly polarized linear down chirp microwave pulse (DCMWP).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the direct coupling between the magnetization and Josephson phase, which allows the manipulation and control of the magnetization through the variation of the Josephson-to-magnetic energy ratio G. Although the reversal in the nanomagnet-Josephson junction system has already been considered with different approaches, in particular, using current pulse [31] or voltage signal [30], the switching time is still larger than the case of the CCP. The minimal amplitude that is able to invert the magnetic state of the NM in the case of CCP (h CCP ) is much smaller than that of the pulses whose frequencies linearly decrease with time: linear chirp pulse h LCP [20] and linear pulse h LP [21], as shown in figure 10 for NM-MW (see figure S.4 in the supplementary material), which enables fast magnetization reversal with low energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the magnetization reversal of single-domain magnetic nanoparticles is important for both fundamental physics and applications [17][18][19]. Various mechanisms have been proposed to achieve the magnetization switching, such as the dc magnetic field and the microwave field with constant frequency, both of which showed long switching time, and the field magnitude should be larger than the anisotropy or coercivity field to energetically stabilize the reversed state [20,21]. Alternative methods, such as the spintransfer and spin-orbit torques assisting reversal, also have their own limitations [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a switching field can be significantly decreased by application of a weak radio frequency field pulse [1][2][3][4][5][6][7][8][9][10]. Magnetization reversal can be achieved exclusively by a microwave field [11], whose amplitude can be reduced provided that the frequency is properly modulated [12][13][14][15][16]. Sun and Wang [17] obtained theoretical limit of the minimal switching field and derived an optimal constant-amplitude pulse yielding the shortest switching time.…”
mentioning
confidence: 99%